Estimation of Forced Convection Heat Transfer Coefficient of Nanofluids using Concept of Colburn Analogy - Azmi, W. H.; Sharma, K. V. (2010)

(untitled)
The concept of Colburn analogy is used in the development of equation for the evaluation of nanofluid forced convection heat transfer coefficients flowing inside a tube. The experiments in the turbulent range of Reynolds numbers with nanofluids of less than 4.0% volume concentration indicate good agreement of the values of friction factor with the Blasius equation. The nanofluid forced convection experimental data available in literature for a wide range of volume concentration, nano materials and particle size is used in the development of the Colburn type equation. The equation developed is in satisfactory agreement with Dittus Boelter and Gnielinski correlations.